Separation of Mineral from Brown Algae Extract using Micro Filtration (MF) and Ultra Filtration (UF) Membrans – Review - Mahreni Mahreni (Eksergi, 2022)
Brown algae (Phaeophyta) contain active compounds such as carbohydrates, proteins, phenolics, fats, pigments, vitamins and minerals. The mineral content of brown algae is around 8% to 40% consisting of cations Na+, K+, Mg++, Fe++, Zn++, Mn++ and heavy metals. Bioactive brown algae has many benefits, including Fucoidan as a cancer drug. The barrier of using Fucoidan as a medicine is its high mineral content. Therefore, the minerals must be separated. The extraction process of brown algae using various methods has been carried out with the aim of isolating the active component of Fucoidan that is free from minerals that will be an obstacle in utilizing the active component. This paper will describe some of the latest methods of extracting the active ingredients of brown algae and mineral separation processes using Micro Filtration (MF) and Ultra Filtration (UF) membrane. MF and UF membrane can separate small molecules such as cations (minerals) that can pass through the membrane so that macromolecules such as carbohydrates, fats, proteins, pigments, phenolics and vitamins can be separated from minerals and active ingredients in the absence of minerals can be obtained. The purpose of this paper is to provide research directions in the exploration of the active ingredients of brown algae for pharmaceutical and cosmetic applications without side effects caused by high metal or mineral content above the threshold value in brown algae extracts.